SAARC Geopolitics and Trade: Missing Intra-regional Connectivity a Hindrance to Further Economic Integration. (March 2015) - Chaturvedi, Pratiksha; Hussain, Zaki; Nag, Biswajit
The South Asian Association for Regional Cooperation (SAARC) region is bestowed with geographical, historical and cultural continuity and yet it remains one of the least integrated regions of the world. This article attempts to analyse the factors inhibiting the economic integration of the region. The intra-SAARC trade is analysed in view of the existence of a free trade agreement between the member nations. The socio-development, infrastructural and economic indicators of the nations are also compared. The reasons for the existence of mistrust and hostility between the SAARC countries are discussed, from India's evident dominant position in the group as a cause for insecurity among other members to the political standoffs between the member nations. While there exists immense potential for greater economic integration and gains from trade, the lack of basic transport-transit connectivity, technical harmonisation and non-tariff barriers are found to reinforce trade costs and inhibit legal trade. Ensuring better connectivity is recognised as a prerequisite by the nations unanimously; however, their political differences have kept them away from making much headway in this regard.